HIGH ORDER THINKING SKILLS: HOW IS IT INTEGRATED WITH COGNITIVE ASSESSMENT? - Andarini Permata Cahyaningtyas; Yunita Sari; Agrissto Bintang Aji Pradana (Jurnal Ilmiah Pendidikan Dasar, 2020)
Curriculum 2013 integrates High-Order-Thinking Skills in the learning process. In primary schools, it has been implemented in 3rd and 6th grade. The activities require students to explore their higher level of thinking in viewing cases. Yet, teachers are not ready to develop any assessment integrated with HOTS, even for cognitive aspects. This research aims to develop a HOTS-based cognitive assessment instrument for third grade students of elementary school. The instrument consists of criteria, questions, answer keys, and scoring guidelines. It is a Research and Development (R&D) with Four-D model: define, design, develop, and disseminate. However, it is only conducted until the third step due to the Covid-19 Crisis. Four experts with major in elementary education studies are assigned as reviewers. The results show that it is developed by using Four-D model. It is also considered to be very valid based on five indicators such as design (0.8), diction and grammar (0.94), content suitability (0.88), completion (0.89), and practicality (0.81). Hence, it is suggested to be used with minor revisions.